Lipoprotein(a) levels and LPA genotype in patients with Familial Hypercholesterolemia - Medeiros, A.M. (2020)
Familial Hypercholesterolemia (FH) patients have na increased cardiovascular risk due to high TC or LDL-C levels. Lp(a) chemical structure is similar to LDL and elevated Lp(a) is considered an independent risk factor for cardiovascular disease (CVD). Recently, it has been described that in patients with high Lp(a), the Lp(a)-C can contribute up to 25% to 50% of all LDL-C. Two LPA variants (rs3798220 and rs10455872) were strongly associated with high Lp(a) levels and increased risk of CVD. In the present work we aim to determine how elevated Lp(a) concentrations and LPA genotype may contribute to clinical phenotype of FH.